Human rights in the light of Maqāṣid al-Sharīʿah - Delagic, Lejla; Ghalia, Bouhedda (IIUM Press, International Islamic University Malaysia, 2018)
The reasearch examines the concept of human rights that is undoubtedly one of the most contested contemporary issues of inter-civilizational and inter-religious forums. The authors emphasize on the etymological, historical and ideological roots of Islamic and contemporary Western notions of rights using the framework of the objectives of Islamic Law (maqāṣid al-Sharīʿah) on this issue. The qualitative methodology in which the textual and comparative analysis is applied on the written materials that are related to the notion of rights and duties of Islam and Western conception of human rights. Finding reveals that the concept of human rights is an important topic of the discourse in the maqāṣid al-Sharīʿahthat is in many aspects cannot be fused with United Nations-backed notion of human rights as the later idea has arisen out of anti-religious secular Western tradition